Efficacy and patient-reported outcomes in advanced non-small cell lung cancer patients receiving aumolertinib as first-line therapy: a real-world study - Li, Hongxin; Zhao, Wen; Chang, Caiyun; Xuan, Tiantian; Wang, Chengjun; Zhang, Rongyu; Yang, Chuang; Wang, Jian; Yi, Cuihua; Wang, Xiuwen; Yu, Shuwen; Li, Jisheng (Frontiers in Pharmacology, 2024)
Background Aumolertinib demonstrated superior progression-free survival (PFS) and a well-tolerated toxicity profile compared to gefitinib in front-line treatment of locally advanced or metastatic non-small cell lung cancer (NSCLC) in the AENEAS trial. However, patient-reported outcomes (PROs) of aumolertinib have not been published. Methods In this real-world study, the efficacy was evaluated by Response Evaluation Criteria in Solid Tumors (RECIST) 1.0. PROs were evaluated using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire C30 (QLQ-C30) and the EORTC Quality of Life lung cancer-specific module (QLQ-LC13) in advanced NSCLC patients receiving aumolertinib as initial therapy. Pre-specified key symptoms were cough, hemoptysis, dyspnea, sore mouth or tongue, dysphagia, hair loss, tingling in hands or feet, chest pain, arm or shoulder pain, and pain at other sites. Results A total of 33 patients were included, 23 of whom had efficacy information up to January 2024. The median follow-up time was 264 days (interval: 36–491 days). The objective response rate and disease control rate were 65.2% and 91.3%, respectively. The EORTC QLQ-LC30 general health status scale showed that functional scales increased and symptom scales decreased during aumolertinib treatment. Symptom scales assessed by the EORTC QLQ-LC13 showed that improvements in cough, sore mouth or tongue, tingling in hands or feet, chest pain, arm or shoulder pain, and other pain sites were both clinically and statistically significant after 6 months of aumolertinib treatment (p < 0.05). Conclusion In this real-world study, aumolertinib showed comparable disease control and objective response rates as reported in the AENEAS trial for advanced NSCLC patients with EGFR-sensitizing mutations. Aumolertinib treatment improved PROs, further supporting it in first-line clinical practice.